2015
DOI: 10.1007/s10854-015-2804-y
|View full text |Cite
|
Sign up to set email alerts
|

Dy3+ and Eu3+ complexes co-doped flexible composite nanofibers to achieve tunable fluorescent color

Abstract: Color-tunable flexible composite nanofibers containing Dy(BA) 3 phen and Eu(BA) 3 phen complexes have been successfully fabricated via a facile electrospinning process. Scanning electron microscopy, energy dispersive spectrometry and fluorescence spectroscopy were used to characterize the samples. The diameter of the composite nanofibers is 420.83 ± 6.55 nm. Tunable color from greenish blue to white to orange can be realized in a single flexible composite nanofiber by varying the mass ratio of Dy(BA) 3 phen-Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Double-crucible technique has been proved to be an efficient, convenient and simple way to fabricate nanofibers, nanobelts and hollow nanofibers [24]. Meanwhile, electrospinning is a promising, straightforward and convenient way to prepare one-dimensional (1D) nanomaterials [25,26] with diameters ranging from tens of nanometers up to micrometers owing to its easy control and low cost, including nanofibers [27,28], core-shell structured nanofibers [29,30], core-shell structured nanotubes [31,32], nanowires [33], nanosheets [34,35] and nanobelts [36][37][38], etc. Nevertheless, the fabrication of PbS or PbSe nanofibers via electrospinning combined with a doublecrucible technique is not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Double-crucible technique has been proved to be an efficient, convenient and simple way to fabricate nanofibers, nanobelts and hollow nanofibers [24]. Meanwhile, electrospinning is a promising, straightforward and convenient way to prepare one-dimensional (1D) nanomaterials [25,26] with diameters ranging from tens of nanometers up to micrometers owing to its easy control and low cost, including nanofibers [27,28], core-shell structured nanofibers [29,30], core-shell structured nanotubes [31,32], nanowires [33], nanosheets [34,35] and nanobelts [36][37][38], etc. Nevertheless, the fabrication of PbS or PbSe nanofibers via electrospinning combined with a doublecrucible technique is not reported.…”
Section: Introductionmentioning
confidence: 99%
“…phosphors [6][7][8]. Our recent work has demonstrated that tunable color and whitelight-emitting can also be achieved by co-doping of dysprosium and europium complexes into polymer-based nanofibers [9]. One-dimensional (1D) nanomaterials with luminescent function can be possibly used as drug carriers, and the drug release amount can be monitored by the variation of luminescence intensity [10].…”
Section: Introductionmentioning
confidence: 99%
“…The precipitates were collected from the solution by magnetic separation, and then dried in an electric vacuum oven at 60°C for 6 h. Dy(BA) 3 phen, Tb(BA) 3 phen, and Eu(BA) 3 phen powders were synthesized according to the traditional method as described in the Refs. [9,24]. 1.8650 g of Dy 2 O 3 was dissolved in 10 mL of concentrated nitric acid and then crystallized via evaporation of excess nitric acid and water by heating, and Dy(NO 3 ) 3 Á6H 2 O powders were acquired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation